Indigenous Knowledge of Cage Aquaculture in Asei Kecil (Kleublouw), Sentani Lake, Papua (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
The traditional knowledge system of cage cultivation reflects the local wisdom of the coastal communities of Sentani Lake, which needs to be documented for the sustainability of traditional livelihood practices. This study aims to analyze the process of constructing fixed net cages (KJT) and floating net cages (KJA), cultivation techniques, and obstacles faced by cultivators. A qualitative descriptive study was conducted in Asei Kecil Village, East Sentani District, from May to August 2023 with six informants (one traditional leader and five cultivators with >2 years of experience) through purposive interviews, participatory observation, and documentation. The results show that the community has mastered cage construction using ironwood for KJT and KJA using traditional techniques. Cultivation practices include selecting quality seeds, providing natural and artificial feed, and gradual harvesting techniques. However, cultivators face obstacles such as environmental fluctuations, predator attacks, and fish theft. Therefore, cultivation requires strengthening the cage security system and knowledge transfer in the form of training on fish disease prevention.